Behavioural dissociation between exogenous and endogenous temporal orienting of attention - Rohenkohl, G; Coull, J; Nobre, A (Public Library of Science, 2011)
Background: In the current study we compared the effects of temporal orienting of attention based on predictions carried by the intrinsic temporal structure of events (rhythm) and by instructive symbolic cues; and tested the degree of cognitive, strategic control that could be exerted over each type of temporal expectation. The experiments tested whether the distinction between exogenous and endogenous orienting made in spatial attention may extend to the temporal domain. Task design and main results: In this task, a ball moved across the screen in discrete steps and disappeared temporarily under an occluding band. Participants were required to make a perceptual discrimination on the target upon its reappearance. The regularity of the speed (rhythmic cue) or colour (symbolic cue) of the moving stimulus could predict the exact time at which a target would reappear after a brief occlusion (valid trials) or provide no temporal information (neutral trials). The predictive nature of rhythmic and symbolic cues was manipulated factorially in a symmetrical and orthogonal fashion. To test for the effects of strategic control over temporal orienting based on rhythmic or symbolic cues, participants were instructed either to "attend-to-speed" (rhythm) or "attend-to-colour". Our results indicated that both rhythmic and symbolic (colour) cues speeded reaction times in an independent fashion. However, whilst the rhythmic cueing effects were impervious to instruction, the effects of symbolic cues were contingent on the instruction to attend to colour. Final conclusions: Taken together, our results provide evidence for the existence of qualitatively separable types of temporal orienting of attention, akin to exogenous and endogenous mechanisms.